Comparative Antibiotic and Probiotic Effects on Antimicrobial Sensitivity of Escherichia coli Isolates and Performance of Broiler Chickens - Ogbu, Cosmas Chikezie; Ibeneme, Nwabueze (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2020)
The study evaluated the growth performance, haematology, serum biochemistry, intestinal microbial count, and antimicrobial resistance profile of Escherichia coli (E. coli) from broiler chicks fed diets supplemented with antibiotics (neomycin, and oxytetracycline), and probiotic (Saccharomyces cerevisiae). One hundred and twenty Abor acre broiler chicks randomly alloted to four treatment groups (30 birds/group; 10 birds/replicate) were used in the 49 days study. Group one (G 1, control) were fed basal diet while G 2, 3, and 4 received basal diet containing S. cerevisiae (0.80g/kg; 108cfu/g), neomycin (0.50g/kg) and oxytetracycline (0.30g/kg), respectively. Results showed significant treatment effects on body weight, feed intake, linear body values, some haematological indices, intestinal, caecal and combined caecal and intestinal bacteria counts, diameter of E. coli inhibition zone, and mortality. Body weight and feed intake were significantly higher in the supplemented groups. Intestinal bacterial count was highest in neomycin and control groups (5.29 Â± 0.01 and 5.22 Â± 0.02 Log10 cfu/ml, respectively) while S. cerevisiae and neomycin groups yielded the highest caecal, and combined caecal and intestinal bacterial counts. Eimeria Oocyst count did not differ significantly between groups. Escherichia coli from antibiotic fed groups had reduced sensitivity or were resistant to the antibiotics. It was concluded that subtherapeutic use of antibiotics as growth promoters in broiler chickens caused the development of antibiotic resistance, and therefore, should be avoided.